Lodzermensche z oblężonego miasta – łodzianie na łamach pamiętnika Cezarego Jellenty „Wielki zmierzch” - Stawiszyńska, Aneta (Acta Universitatis Lodziensis. Folia Historica, 2014)
The diary kept by a writer from Warszawa, C. Jellenta, presents the initial months of the First World War from the point of view of a citizen of Warszawa. Jellenta, who was observing the outbreak of the great conflict with interest and devotion, frequently presented the fortunes and misfortunes of Łódź’s citizens in the context of fights taking place in a close proximity to the city. The writer was a passionate observer of, in his opinion, a significant change of the profile of a statistical citizen, which was caused by the calamitous events taking place between November and December 1914. Finally, after taking part in numerous meetings with the refugees from Łódź, Jellenta characterized the possibility of irreversible internal changes among the Lodzermensche as unlikely. Moreover, he frequently pointed out that the fights taking place near Łódź may be considered as a clash of two natural forces – the German and Slavonic elements. Such an understanding of the conflict may be considered as a clear reference to the battle of Grunwald.